Utilization of Thermal-Activated Coal Gangue to Enhance the Properties of Sandy Soil Composites - Wangtao Fan; Ruofan Liu; Runxia Zhang; Xiaoguang Chen; Jin Li; Aochen Zhang; Jing Qian; Zhaolin Gu; Jianyun Wang (Applied Sciences)
To effectively solve the problem of land sanding and improve the water- and element-retaining properties of sandy soil, a thermal-activated coal gangue (TACG) was used as an ameliorating material to prepare a composite soil mixed with sandy soil to enhance the water-retaining and fertilizer-fixing properties of the sandy soil and reduce the evaporation of water in the soil. The structure and thermal stability of the gangue were characterized using Fourier transform infrared spectroscopy and thermogravimetric analysis. By applying different dosages and different calcination temperatures of the TACG, the water-holding capacity of the mixed soil was determined, and changes in pore structure were observed. When the dosage was 15% and the calcination temperature was 600 °C, the mixed soil possessed the most excellent distribution of pore structure and could effectively prevent water evaporation. Meanwhile, the application of the TACG in sandy soil improved its adsorption of K+, which showed the potential application of thermally activated gangue materials in the field of soil improvement.